2017
DOI: 10.15850/ijihs.v5n1.960
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Cisplatin-resistant Human Breast Cancer MCF-7 Cell Line

Abstract: Objective: To evaluate morphological changes of breast cancer cell line MCF-7 following the development of acquired resistance towards cisplatin. Resistance towards anticancer agents still plays an important role in the breast cancer chemotherapy failure. Methods:The cisplatin resistant subline MCF-7/CisR was developed in-vitro by cultivating the parental cell line cisplatin-sensitive MCF-7 with raising concentration of cisplatin (from 0.01 to 2.3 µM) for four months. The cell morphology was observed by giemsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Clinical trials with Sorafenib showed that this drug can prolong survival in HCC patients, but its efficacy is limited due to development of resistance in cells [422] and size in chemoresistant cancer cells [423,424]. Furthermore, the toxic dose of Sorafenib did not cause a statistically significant decrease in cell viability compared to the clinical dose, while HepG2 showed a significant statistical increase in cell death compared to the clinical dose.…”
Section: Sorafenib Treatmentmentioning
confidence: 98%
“…Clinical trials with Sorafenib showed that this drug can prolong survival in HCC patients, but its efficacy is limited due to development of resistance in cells [422] and size in chemoresistant cancer cells [423,424]. Furthermore, the toxic dose of Sorafenib did not cause a statistically significant decrease in cell viability compared to the clinical dose, while HepG2 showed a significant statistical increase in cell death compared to the clinical dose.…”
Section: Sorafenib Treatmentmentioning
confidence: 98%
“…A cell population is considered to be resistant when it increases its baseline tolerance, managing to proliferate in a medium with twice, or more than twice, the drug concentration tolerated by the parental line, for which mechanisms are activated that allow it to avoid drug-induced cell death, which is related to morphological variations described as an increase in cell size, increase in the nucleus–cytoplasmic ratio, irregularities in the cell membrane borders, or an increase in cytoplasmic granules [ 25 , 26 , 27 ].…”
Section: Resistance To Cisplatin Treatmentmentioning
confidence: 99%
“…Drug-induced necrosis leads to swelling of organelles and disruption of plasma membrane, but it can be triggered by stimuli shared with extrinsic apoptosis. 19,20 The morphological changes associated with drug resistance include the emergence of irregular cell shape in pancreatic cancer, 21 larger and irregular-shaped cells of high nucleus to cytoplasm ratio in breast cancer, 22,23 spindle-like shapes and diffusive plasma membrane shape 24 in colon cancer HCT8 cells and elongated and irregular fibroblastoid morphology for drug-resistant ovarian cancer cells versus that of drugsensitive cells. 25 Cell proliferation assays have traditionally guided in vitro drug sensitivity studies, but these cannot distinguish the cell death mechanism and they cannot be conducted with singlecell sensitivity to quantify the subpopulations in heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%